Raising the bar (21). Issue 3 (3rd July 2022) - Elhorst, Paul; Abreu, Maria; Amaral, Pedro; Bhattacharjee, Arnab; Bond-Smith, Steven; Chasco, Coro; Corrado, Luisa; Ditzen, Jan; Felsenstein, Daniel; Fuerst, Franz; McCann, Philip; Monastiriotis, Vassilis; et al.
ABSTRACT: This editorial summarizes the papers published in issue 17 (3) (2022). The first paper analyses the impact of knowledge spillovers on patent applications using a Tobit model. The second paper sets out an economic-theoretical model of industrial specialization patterns across cities and their impact on the spatial agglomeration of skilled workers and long-term productivity growth. The third paper analyses the price and average cost functions of a competitive industry in which firms face diseconomies of scale but enjoy economies of scale when they agglomerate. The fourth paper shows that productivity spillover effects and their endogeneity are key to understanding the productivity-compensation gap. The fifth paper studies geographical and sectoral specialization versus concentration of global supply chains. The sixth paper combines spatial autoregressive (SAR) and geographically weighted regression (GWR) models to test whether urban residents have reacted to the Covid-19 pandemic by moving out of US metropolitan centres into the suburbs. The seventh paper investigates the impact of natural disasters caused by climate change on forced outmigration flows in South and South-East Asian countries.